Performance analysis of modeling scale on multiband oscillations in grid-connected wind farm - Zhu, Lin; Chen, Leke; Hu, Peiyan; Wu, Yue; Liao, Mengjun; Xu, Min (Frontiers in Energy Research, 2023)
Grid-connected PMSG wind farms may be susceptible to oscillation when connected to weak grids. At present, it is generally accepted in academic circles that PMSG oscillations are affected by grid strength and converter control. However, there is no consensus on the specific source of oscillation. This paper explores this issue from two perspectives: the model and the oscillation frequency band. First, the small signal model of the PMSG wind farm grid-side system is established and compared with the PMSG full-order electromagnetic transient model in MATLAB/Simulink to evaluate the performance accuracy of the small signal model for small perturbations. Then, based on the eigenvalue analysis of the small signal model, two dominant modes are identified: the subsynchronous oscillation mode and the low-frequency oscillation mode. The study of the influencing factors shows that the former is closely related to the DC voltage control and the dynamics of DC link, and is hardly affected by grid strength. On the other hand, the latter is significantly weakened with the decrease in grid strength, and it is closely related to the PLL control. Finally, time-domain simulation is used to verify the theoretical analysis, and the conclusions can provide a reference for tuning the control parameters of PMSG converter.